FORCEJEO POR MANTENER EL AGUA LIMPIA Y EL SUSTENTO DIARIO: La minería canadiense en Costa Rica en la era del desarrollo sustentable/globalización - Isla, Ana (2023)
One of the major social tensions today is between the demands of private capital and ‘national’ governments for economic growth and globalization, and the demands of local communities for security and livelihoods. In Costa Rica, the territorial dynamics is in intense transformation due to the sustainable development agenda that promises to confront the debt and environmental crises, through economic growth. Since 1991, when sustainable development has been implemented in the Arenal Conservation Area and its surroundings, an avalanche of Canadian mining companies interested in strip gold mining exploitation has alarmed women and men of local communities, because the mining operation has been expanded to areas never before linked to mining. In this paper, I will illustrate a battle of women for clean water and livelihood, and their resistance to Canadian mining that want to get access to the land to search for gold.